Сумарний вміст іонів в листках рослин різного еволюційного рівня - Medvedev, V.A.; Ilyenko, A.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
A possibility of use the electric conductivity value, reflecting the total content of ions in water extracts from the leaf, to estimate the level of evolutionary development of plants has been studied. The authors have investigated 692 species belonging to 254 genus and 93 families. The natural increase of electric conductivity value in lines is revealed: gymnospermous –> angiospermous; trees –> bushes –> herbs.